2020
DOI: 10.1115/1.4048738
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Sister Holes Film Cooling With Various Secondary-to-Primary Hole Diameter Ratios

Abstract: For increased specific thrust and efficiency, more effective film cooling schemes are developed with each successive gas turbine design. Adding secondary film cooling holes to each primary film cooling hole represents such improvement without significantly increasing cost. Presented is an experimental investigation on the effects of secondary-to-primary hole diameter ratio on film cooling performance and flow structure in the coolant-to-passage flow merge zone. Film cooling effectiveness values and heat transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recently Zhou et al 31 and Zhu et al 32 studied the effects of diameter ratio between primary hole and secondary hole, numerically and experimentally, respectively. Zhou et al 31 showed that the larger secondary holes provide better cooling effectiveness while the experimental results of Zhu et al 32 consistent with these results. The work of Zhou et al 31 made at constant exit area while Zhu did change the exit areas but keeps the blowing ratio constant with the changing mass flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Zhou et al 31 and Zhu et al 32 studied the effects of diameter ratio between primary hole and secondary hole, numerically and experimentally, respectively. Zhou et al 31 showed that the larger secondary holes provide better cooling effectiveness while the experimental results of Zhu et al 32 consistent with these results. The work of Zhou et al 31 made at constant exit area while Zhu did change the exit areas but keeps the blowing ratio constant with the changing mass flow rate.…”
Section: Introductionmentioning
confidence: 99%